Personalised peptide vaccination combined with radiotherapy for patients with advanced hepatocellular carcinoma: a phase 1 study. (September 2017) - Shen, Jie; Zou, Zheng-Yun; Wang, Li-Feng; Yan, Jing; Kong, Wei-Wei; Meng, Fan-Yan; Chen, Fang-Jun; Du, Juan; Shao, Jie; Xu, Qiu-Ping; Li, Ru-Tian; Wei, Jia; et al.
Abstract: Background: We aimed to investigate a new treatment method for the treatment of advanced hepatocellular carcinoma. The method was a cellular immune therapy based on personalised peptide vaccination (PPV-DC-CTL) combined with radiotherapy. Methods: We did a phase 1 study in which patients with advanced hepatocellular carcinoma who were not eligible for surgery, as confirmed by multidisciplinary consultation, were treated with precise radiotherapy combined with PPV-DC-CTL in the Comprehensive Cancer Centre of Nanjing Drum Tower Hospital, Nanjing, China. To personalise the vaccine, the peptide candidate library, including mutated peptides and highly expressed peptides, was established according to the gene mutation and expression spectra of hepatocellular carcinoma and previous studies about PPV. Peptides for vaccination of every patient were selected from the peptide candidate library, with the consideration of the pre-existing immunity of the host before vaccination. The assay of peptide-specific IFN-γ production was used to define pre-existing immunity. Side-effects were measured with a haemogram. This study is registered with the Chinese Clinical Trial Registry, number ChiCTR-OIC-16010025. Findings: A total of nine patients with advanced hepatocellular carcinoma were admitted. Four patients had multiple liver metastases (liver lesions more than three pieces), one patient had liver metastasis and portal vein tumour thrombosis, one patient had lung and bone metastases, two patients had liver and lung metastases, and one patient had liver metastasis and peritoneal metastasis. Following radiotherapy and 1–3 cycles of PPV-DC-CTL treatment, AFP concentrations were significantly reduced in six patients compared with baseline concentrations, and imaging assessment of the lesions showed a partial response in three of the patients and stable disease in the other three patients. An objective response was achieved in 33% and disease control in 66%. This regimen was found to be safe and well tolerated because none of the patients developed liver or kidney side-effects. Only one patient developed grade 2 bone marrow suppression, and the other patients had no significant side-effects. Interpretation: Radiotherapy combined with PPV-DC-CTL provides a new therapeutic strategy for patients with advanced hepatocellular carcinoma, which is well tolerated, safe, feasible, and effective. Funding: National Natural Science Foundation of China, Jiangsu Provincial Medical Youth Talent, and the Key Medical Science and Technology Development Project of Nanjing.